Five year development plan for Bureau of Standards Dominica - Henry, Artnel S. (CARICOM Secretariat GeorgetownGY, 2001)
Provides an organized program of proposals and guides for the managers of the bureau, in the development of an organization that will function efficiently and become a catalyst for sustainable economic growth.